Analisis Strategi Pemasaran Konvensional Pada UMKM Kacang Goreng Kletik Sonic Jaya Dalam Memepertahankaan Eksistensi Di Era Digitalisasi - Oktanita, Andriya; Inayah, Anisa Afri; Saputra, Aditiyo Dwi; Putri, Puspita Lianti (Universitas Dharmawangsa, 2025)
This study is related to conventional marketing strategies implemented by UMKM Kacang Goreng Kletik Sonic Jaya in maintaining its existence in the digital era. The main issue in this study is the dependence of UMKM on traditional marketing strategies such as word of mouth, even though current market competition increasingly relies on digital technology. The purpose of this study is to analyze the effectiveness of conventional marketing strategies in maintaining the existence of UMKM in the midst of the digital era. This study uses a qualitative descriptive approach, with data collection methods in the form of interviews and documentation of UMKM owners and environments. The results of the study indicate that although conventional strategies are still quite effective in the local market, especially in the Pemalang area, there are obstacles in terms of adopting digital technology that can limit market growth. UMKM have limited knowledge and resources to access digital platforms. Therefore, training is needed on digital marketing so that UMKM can increase competitiveness and expand market reach more widely.